Photochemical reactivity of matrix-isolated monomeric carboxylic acids - Fausto, R. (2001)
When used together with conventional spectroscopic methods (e.g. infrared spectroscopy), matrix isolation constitutes a very convenient technique to undertake photochemical studies on single molecules that are not easily accessible to experiment under other sampling conditions, such as carboxylic acid monomers, which show a strong tendency to aggregate. Once a matrix of a given substance has been prepared, in situ irradiation of the target matrix-isolated molecule at a proper wavelength enables the promotion of different types of photochemical processes which, most of times, can also be easily probed spectroscopically. These include conformational interconversions, tautomerization reactions and fragmentation processes (including photodegradation reactions). In this paper, results of both electronic and vibrational photochemical studies carried out on a series of different matrix-isolated carboxylic acid monomers are presented. Besides more conventional techniques, an approach based on irradiation at a frequency matching that of the first overtone of a particular vibrational mode is described.